The Role of Ethical Leadership in Achieving Sustainable Performance (Comprehensive Journal of Science, 2026)
This study aimed to identify the role of ethical leadership in achieving sustainable employee performance. The study was conducted at Mellitah Oil and Gas Company. A descriptive methodology was employed, utilizing a questionnaire to collect data. The study population consisted of Mellitah Oil and Gas Company employees, from whom a stratified random sample of 160 employees was selected. To achieve the study objectives, the questionnaire was used as the data collection tool. The data collected was analyzed using the SPSS statistical software. The analysis relied on arithmetic means and standard deviations for each dimension of the two variables, correlation coefficients, and multiple regression analysis. The study concluded with several key findings, the most important of which is:The level of application of ethical leadership principles was high across all criteria used in the study. This is based on the respondents' responses regarding the application of ethical leadership principles collectively. This is attributed to the fact that the company's leadership adopts ethical leadership principles, which are clear ethical values ​​and standards based on justice, honesty, integrity, respect for others, and striving to serve the public good.